Lonely Voices Crying in the Wilderness - Garrou, Thomas J. (East Carolina University, 2012)
This text is a work of creative fiction that delves into the minds of those who have experienced conflict. Whether it is during war or life situations, these stories are often internalized. The text explores how the young are more resilient to casualties and are more apt to mend. We call it a rite of passage. Those who are part of a battle might not be able to compartmentalize their emotional expenditures. This we call PTSD. The text explores two men's different approaches to handling the stresses of war, their ideologies, and their ways of mending.
Keywords: American studies; Ideology; Loss; PTSD; Revenge; Snipers; War; Stress (Psychology)--Fiction; War--Psychological aspects--Fiction; Post-traumatic stress disorder--Fiction